Examination of the Steps and Attachment Circumstances of the Poly Lactic-co-glycolic Acid (PLGA) Nano-particle to Increase the Effect of Nanomedicine on Vancomycin-Resistant Enterococcus Faecalis - Rafian, Bahare; Eghdami, Anoosh; Moradi, Gholamali (Novelty in Biomedicine, 2018)
Background: Infectious diseases continue to be one of the biggest health challenges around the world, followed by problems caused by antibiotic resistance and excessive use of antibiotics. In general, Enterococcus faecalis is the main cause of nosocomial infections and is the most common cause of surgical ulcer infections. This study examines how a vancomycin nanomedicine attaches to poly lactic-co-glycolic acid (PLGA) nanoparticle. Determining the role of vancomycin nanomedicine on reducing the drug resistance of vancomycin in E. faecalis (clinical hospital isolates) and determining the cytotoxicity effects of nanomedicine. Materials and Methods: In this method, first, attachment made through chemical processes such as emulsion between vancomycin antibiotic and a PLGA nanoparticle, and resultant antibiotic tested on vancomycin resistant E. faecalis. Results: The results of this study indicate that the method of nanomedicine attachment to antibiotics was an effective method and it was determined by X-ray Diffraction that the attachment was precisely performed. In the antibiogram method, the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) of the nanomedicine increased in respect to vancomycin antibiotic. Conclusion: The results showed that produced Nano-antibiotics had a better effect than resistant antibiotics.